2010
DOI: 10.1177/0143034309352267
|View full text |Cite
|
Sign up to set email alerts
|

Peer Aggression and Mental Health Problems

Abstract: This study examined whether self-esteem mediates the association between peer aggression and internalizing and externalizing problems in adolescents. A total of 204 Swedish adolescents aged between 12- and 16-years-old completed self-report measures; self-esteem was assessed with ‘I think I am’ (ITIA) and internalizing and externalizing problems with Youth Self-Report (YSR). Our results showed that internalizing problems in peer aggressors could be understood as problems with low self-esteem, while internalizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 50 publications
2
29
0
2
Order By: Relevance
“…Whereas negative self-evaluations and self-esteem mediated school adjustment and achievement (Graham et al 2006;Lopez and DuBois 2005;Raskauskas et al 2015) and externalizing problems (Ybrandt and Armelius 2010), findings were more mixed with respect to internalizing outcomes and might be dependent on other individual or contextual factors. Similarly, self-blame did not emerge as a stable mediator although tested repeatedly and with respect to different outcomes (Chen and Graham 2012;Graham et al 2006;Harper 2012;Perren et al 2013).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Whereas negative self-evaluations and self-esteem mediated school adjustment and achievement (Graham et al 2006;Lopez and DuBois 2005;Raskauskas et al 2015) and externalizing problems (Ybrandt and Armelius 2010), findings were more mixed with respect to internalizing outcomes and might be dependent on other individual or contextual factors. Similarly, self-blame did not emerge as a stable mediator although tested repeatedly and with respect to different outcomes (Chen and Graham 2012;Graham et al 2006;Harper 2012;Perren et al 2013).…”
Section: Discussionmentioning
confidence: 82%
“…Several studies (Harper 2012;Lopez and DuBois 2005;Perren et al 2013;Singh and Bussey 2011;Ybrandt and Armelius 2010;You and Bellmore 2012) utilized Achenbach's measures (Achenbach et al 2003), specifically the Youth Self-Report, Child Behavior Checklist, and Teacher Report to assess associations between peer victimization and externalizing problems, though studies varied with respect to the mediator tested. For instance, Lopez and DuBois (2005) and Ybrandt and Armelius (2010) found that lower levels of self-esteem partly explained why victimized adolescents showed greater externalizing problems and Harper (2012) found that self-blame was to some extend responsible for victim's higher risk for externalizing problems.…”
Section: Mediators On Associations Between Peer Victimization and Extmentioning
confidence: 99%
See 1 more Smart Citation
“…Niveles bajos en los jóvenes se han asociado con síntomas psicopatológicos como reacciones de ansiedad 12 , depresión, desesperanza y tendencias suicidas 13 , demoras innecesarias en la realización de tareas y son comúnmente observados en aquellos que presentan conductas agresivas 14 , conductas antisociales 15 o violencia escolar 16 .También es fundamental analizar que los niños y jóvenes con baja autoestima se caracterizan por presentar una peor salud física, encontrando que los sujetos que llegan a la adolescencia con baja autoestima tienen un riesgo mayor de presentar hábitos no saludables y una salud mental más pobre 17 .…”
Section: E L Ministerio De Salud De Chile a Través Deunclassified
“…certains facteurs protecteurs d'ordre intrapersonnel, interpersonnel et scolaire ont été identifiés chez les adolescents et adolescentes victimes d'intimidation, à caractère homophobe ou autre. les facteurs intrapersonnels facilitant la résilience comprennent surtout l'estime de soi qui permet une meilleure acceptation de soi (elze, 2003 ;Fenaughty et harré, 2003 ;Ybrandt et armelius, 2010) et les stratégies d'adaptation psychologique, telles que demander de l'aide, ventiler les émotions ou éviter les lieux d'agressions. ceci peut être aidant pour régler le problème ou du moins en gérer les aléas émotifs (baldry et Farrington, 2005 ;brady, tschann, pasch, Flores et ozer, 2009 Farrington, 2005 ;espelage, aragon, birkett et Koenig, 2008 ;saewyc et al, 2009 ;stadler, Feijel, rohrmann, vermeiren et poutska, 2010 ;Werner, 2005 ;Yeung et leadbeater, 2010 d'autres variables protectrices étudiées relèvent de l'environnement scolaire.…”
Section: Facteurs De Protection Et Processus De Résilienceunclassified